First Record and Molecular Identification of Amantia Manginiana in Jordan - Al-Momany, Ahmad Mohamad; Hasan, Hanan Aref; Al-Abdallat, Ayed M. (Jordan Journal of Agricultural Sciences, 2022)
The occurrence of the basidiomycete Amantia manginiana is reported for the first time in Jordan. The large crumbly white wild mushroom was collected from woodland during December 2014 from Dabouq in Jordan. All morphological characteristics including cap, stem, gills, and spores were recorded. The mycelium was isolated by aseptically removing a small part of the fruiting body and transferring it onto the potato dextrose agar plate. After four days of incubation at 25-30 °C in the dark, a pure culture was obtained. Sequence analysis of a partial fragment of 28S nuclear large subunit (nLSU) in the ribosomal RNA gene of the isolated strains included the new strain within taxon Amanita manginiana with 95% similarity to Genebank accession No. KP161281 and 91% to Genebank accession No. AF024463.1 respectively. According to morphological characteristics and molecular sequence analysis, the mushroom was identified as Amanita manginiana and recorded for the first time in Jordan.